ANALYSIS OF THE FORMATION SOURCES OF THE GALVANIC SLIMES AND POSSIBILITIES OF THEIR EFFECTIVE UTILIZATION WITH USING IN MACHINE-BUILDING COMPLEX OF THE REPUBLIC OF BELARUS - A. S. Panasugin; S. L. Rimoshevski; D. E. Ivanov; D. P. Mihalap; N. I. Bestuzhev; Ju. B. Sivak (Литьë и металлургия, 2005)
А brief analysis of formation of the galvanic production wastes in machine-building complex of the Republic of Belarus is given.